Interventions for promoting reintegration and reducing harmful behaviour and lifestyles in street-connected children and young people: a systematic review - Coren, Esther (Campbell Systematic Reviews, 2016)
This review assessed the effectiveness of interventions for improving outcomes among street-connected children and young people, and for reducing some important health-related risks; and to improve access to and integration into society, education, and employment opportunities.